1992
DOI: 10.1111/j.1365-2362.1992.tb01473.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic hepatic clearance of indocyanine green in the pig: Dependence on plasma protein concentration

Abstract: Intrinsic hepatic clearance (K) of indocyanine green (ICG) is used as a quantitative measure of liver function. ICG is tightly bound to plasma proteins. The purpose of this study was to examine the effect of changes of plasma protein concentration on K in anaesthetized pigs with intact hepatic circulation. In addition, an attempt was made to evaluate the corresponding changes of the unbound intrinsic clearance of ICG. The plasma protein concentration was changed by exchange of plasma with either dextran-70 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Although ICG clearance is widely used to estimate liver blood flow, the technique may involve significant assumptions, 33 including that of instantaneous distribution into the plasma compartment, changes in plasma protein concentration that may unpredictably alter intrinsic hepatic clearance of ICG, 34 incomplete extraction, 35 and the accuracy of the assay. 36 However, ICG administration to estimate hepatic blood flow has been considered an especially useful approach in comparative studies.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Although ICG clearance is widely used to estimate liver blood flow, the technique may involve significant assumptions, 33 including that of instantaneous distribution into the plasma compartment, changes in plasma protein concentration that may unpredictably alter intrinsic hepatic clearance of ICG, 34 incomplete extraction, 35 and the accuracy of the assay. 36 However, ICG administration to estimate hepatic blood flow has been considered an especially useful approach in comparative studies.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…The doses of ICG were selected on the basis of the data from Rikkers and Moody [23]. Blood samples were collected from the left tail vein before and 2, 4, 6, 10, 15, 20 and 30 min after ICG injection according to a previously reported procedure [2, 9, Indocyanine green (ICG), a tricarbocyanine dye, is normally used to assess hepatic function by measuring the plasma retention of this dye after intravenous administration to either animals [4,7,14,20] or human beings [1,7,15]. ICG possesses various advantages as compared to sulfobromophthalein (BSP); distribution in the plasma volume without extravascular distribution, removal exclusively by the liver into bile without biotransformation, lack of enterohepatic circulation [12,15,19] and low incidence of adverse reactions [1].…”
Section: Animalsmentioning
confidence: 99%
“…3 ICG binds to blood plasma proteins immediately after injection and is cleared from the circulation in approximately 20 minutes. 4,5 Recently, Matsuda et al 6 reported observation of ICG-labeled cells in retinal and choroidal vessels after dye clearance from the plasma. Based on their size and number, the ICG-labeled cells were thought to be circulating leukocytes.…”
mentioning
confidence: 99%